Dermatophyte Profile in Patients with Dermatophytosis in Polyclinic Dermatology and Venerology of the General Hospital Dr. Ferdinand Lumbantobing Sibolga in 2019 - May Iyasya Sarumpaet; Dian Dwi Wahyuni (Talenta Publisher, 2021)
Dermatophytosis is a superficial skin infection caused by dermatophytes that infected keratinous skin tissue, dermatophytes form molecules that bind to keratin as a source of nutrients in the formation of colonization. Dermatophytes that cause dermatophytosis are Tricophyton sp, Epidermophyton sp and Microsporum sp. To find out the Profile of dermatophytes in patients with dermatophytosis in the Polyclinic of Dermatology and Venerology Dr. Ferdinand Lumbantobing Sibolga in 2019 conducted observational research with cross sectional design. The sample of this study were 75 patients who were new patients and had not used antifungal drugs. This sample is then examined by examination of KOH and cultured and then identified by Scotch-tape Preparation in a microscope. The prevalence of dermatophytosis in this study was 23% of skin cases. The majority of dermatophytosis patients are women (52%), the most age group is 46-65 years (30.7%) and is most often found in housewives (24%). The dermatophytes species found were Trichophyton rubrum, Trichophyton mentagrophytes and Microsporum canis with the most species Trichophyton rubrum (37.3%), which was then followed by Trichophyton mentagrophytes (16%). Tinea corporis, tinea cruris, tinea capitis, tinea pedis and tinea unguinum are dermatophytosis cases that were found in this study. It can be concluded that Trichophyton rubrum is the most common cause of dermatophytosis in Dr. Ferdinand Lumbantobing Sibolga with Tinea corporis is the most classified classification of dermatophytosis.